2021
DOI: 10.1096/fj.202002284rr
|View full text |Cite
|
Sign up to set email alerts
|

The hippo pathway: A master regulator of liver metabolism, regeneration, and disease

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 283 publications
(732 reference statements)
0
30
0
Order By: Relevance
“…MST1/2-dependent phosphorylation leads to activation of LATS1/2, which culminates in phosphorylation YAP and TAZ preventing their import into the nucleus and terminating expression of YAP/TAZ-dependent target genes. Numerous proteins involved in regulation of cell growth, polarity, and homeostasis regulate activity of Hippo signalling pathways (for recent reviews see [ 4 , 5 ]).…”
Section: Introductionmentioning
confidence: 99%
“…MST1/2-dependent phosphorylation leads to activation of LATS1/2, which culminates in phosphorylation YAP and TAZ preventing their import into the nucleus and terminating expression of YAP/TAZ-dependent target genes. Numerous proteins involved in regulation of cell growth, polarity, and homeostasis regulate activity of Hippo signalling pathways (for recent reviews see [ 4 , 5 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The Hippo pathway plays an important role in regulating stem cell proliferation and apoptosis [45,46]. Previous studies have shown that the activated Hippo pathway can inhibit cell proliferation and promote cell apoptosis of the intervertebral disc cells [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Pathways were characterized by the number of hits (the number of genes targeted by differentially expressed miRNAs) and the significance of enrichment ( p < 0.05). The Hippo signaling pathway plays a crucial role in the processes of apoptosis, proliferation, and cell regeneration ( Nguyen-Lefebvre et al, 2021 ). The Hippo signaling pathway is an essential modulator of liver metabolism ( Koo and Guan, 2018 ), acting through the hormone receptor GPCR.…”
Section: Discussionmentioning
confidence: 99%